Preparation and Characterization of Tin(II) and Tin(IV) Complexes with Some Morpholine-N-Thiocarbazones - JHA, R.R.; JHA, D.K. (Asian Journal of Chemistry, 2010)
Complexes of Sn(ll) and Sn(IV) with benzaldehyde morpholine-N-thiocarbazone (Benzmtcz-H), cinnamaldehyde morpholine-N-thiocarbazone (Cinmtcz-H), Cyclohexanone morpholine-N-thio-carbazone (Cyclmtcz-H), isatine morpholine-N-thiocarbazone (Istmtcz-H), Salicylaldehyde morpholine-N-thiocarbazone (Salmtcz-H2) and o-hydroxyacetophenone morpholine-N-thiocarbazone (Ohacetpmcz-H2) of composition Sn(lI)(LH)2Cl2; (LH = Benzmtcz-H, Cinmtcz-H, Istmtcz-H, Cyclmtcz-H), [Sn(II)(LH)2]; (LH2= Salmtcz-H2 or Ohacetpmtcz-H2), [Sn(IV)L2] and [Sn(IV)LI2] (LH2 = Salmtcz-H2 or Ohacetpmtcz-H2 and [Sn(IV)L2I2]; (LH = Benzmtcz-H, Cinmtcz H or Cyclmtcz H) have been prepared and characterised by elemental analysis, electrical conductance, IR and NMR spectral studies.